Penyuluhan Bahaya Anemia Pada Remaja Di SMK Kesehatan Fania Salsabila - Ahzani, Yersi; Kurniasari, Winna (STIKES Advaita Medika Tabanan, 2024)
Anemia is a condition where the blood hemoglobin level is less than the threshold. Physiologically, anemia occurs when there is a lack of hemoglobin to transport oxygen to the tissues. Anemia is one of the most common health problems found in teenage girls. Anemia in teenagers can have a negative impact on the health and future of teenagers. Objective: to increase the knowledge of Fania Salsabila Health Vocational School students regarding the meaning, causes, types, symptoms, preventing and treating anemia. Method: lecture and using animated video media as well as question and answer with a total of 20 participants, class XII Nursing Assistant students at the Fania Salsabila Health Vocational School. Conclusion: counseling about the dangers of anemia in adolescents was received well and smoothly, students actively asked questions and were interested in the topic presented. Suggestion: schools are expected to continue the program of providing blood supplement tablets in collaboration with the health service as an effort to prevent anemia in adolescents. Key words: Anemia; Counseling; Adolescence